Growth Red Spinach (Amaranthus amoena) by Hydroponics Using Charcoal Media Husk - Isherdini, I; Nurlaila, Dyah Salma; Suparti, S (Universitas Muhammadiyah Surakarta, 2023)
Red spinach is a vegetable plant of the most common varieties of spinach. This plant has good content for the body such as vitamin A, vitamin C, protein and high polyphenols antioxidants content. Red spinach production in Indonesia is still very low. This can happen because the majority of our people are not very familiar with red spinach and cause its cultivation and marketing to be not very intense. Hydroponics is a farming method without using soil media, but with nutrient solutions or other materials that contain nutrients. The aim of the study was to find out the differences and yields of red spinach plants if the concentration of AB MIX fertilizer was different. The research used the research method used was experimental with an environmental design in the form of a Factorial Randomized Block Design (RBD), with 5 treatments. P0 = husk charcoal, P1 = husk charcoal + 1000 ppm, P2 = husk charcoal + 800 ppm, P3 = husk charcoal + 1200 ppm, P4 = husk charcoal + 600 ppm, and P5 = husk charcoal + 1400 ppm. Analysis using the Honest Significant difference Test (BNJ) with a level of 5% was carried out to determine whether there was an interactions of each treatments. The results showed that the best treatments was P1 with a plant heights of 1.5 cm, a leaf width of 0.7 cm, and a total of 6 leaves.